An Indonesian Translation of "COVIBOOK": A Critical Review - Sujatna, Meita L.; Siregar, Alvii T.B. (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this work is to critique an Indonesian translation of "COVIBOOK." The book is part of a series of children's literature that introduces what the coronavirus do and how children should approach the epidemic and how to protect themselves against it. By comparing the English and Indonesian text versions, the study used Berman's methodology to conduct a systematic evaluation and Molina and Albir and Newmark to check the method and techniques of translation. Text function consistency was shown to have a high level of adherence at a macro level, catering to educate young readers about the virus and its impacts. However, on a micro level, several expressions were transformed into adult-level and less-current language. To better depict the original text, it might be concluded that it should employ a more contemporary children's language level.